Reforming the EU Energy Tax Directive: Assessing the Options - Ian Parry; Herman R. J. Vollebergh (Center for Economic Studies and ifo Institute (CESifo), 2016)
The efficiency case for raising fuel tax minima under the EU Energy Tax Directive (ETD) appears nuanced. Some fuels may be undertaxed (e.g., road diesel, natural gas), while others may be adequately taxed already (e.g., gasoline). Reform proposals would increase some minima, including for road diesel and natural gas, while leaving that for gasoline unchanged. This is a step in the right direction, though the climate, fiscal, health, and net economic benefits are limited. There are potentially much larger gains from extending tax minima to fuels (especially coal) covered by the EU Emissions Trading System (if the cap is tightened). Two-speed systems (with lower minima for low-income countries) may improve political acceptability, while sacrificing little in terms of climate benefits. Under higher, but still plausible, environmental damage assumptions than used here, there is a case for reviving ETD reform, whatever its exact structure.
Keywords: Q54; Q58; H23; 330; energy tax directive; climate; tax floor; efficiency